Influence of Physical-Chemical Soil Parameters on Microbiota Composition and Diversity in a Deep Hyperarid Core of the Atacama Desert - Fuentes, Bárbara; Choque, Alessandra; Gómez, Francisco; Alarcón, Jaime; Castro-Nallar, Eduardo; Arenas, Franko; Contreras, Daniel; Mörchen, Ramona; Amelung, Wulf; Knief, Claudia; Moradi, Ghazal; Klumpp, Erwin; et al. (Frontiers in Microbiology, 2022)
The extreme environmental conditions and lack of water on the soil surface in hyperarid deserts hamper microbial life, allowing only highly specialized microbial communities to the establish colonies and survive. Until now, the microbial communities that inhabit or have inhabited soils of hyperarid environments at greater depths have been poorly studied. We analyzed for the first time the variation in microbial communities down to a depth of 3.4 m in one of the driest places of the world, the hyperarid Yungay region in the Atacama Desert, and we related it to changes in soil physico-chemical characteristics. We found that the moisture content changed from 2% to 11% with depth and enabled the differentiation of three depth intervals: (i) surface zone A (0-60 cm), (ii) intermediate zone B (60-220 cm), and (iii) deep zone C (220-340 cm). Each zone showed further specific physicochemical and mineralogical features. Likewise, some bacterial phyla were unique in each zone, i.e., members of the taxa Deinococcota, Halobacterota, and Latescibacterota in zone A; Crenarchaeota, Fusobacteriota, and Deltaproteobacterium Sva0485 in zone B; and Fervidibacteria and Campilobacterota in zone C, which indicates taxon-specific preferences in deep soil habitats. Differences in the microbiota between the zones were rather abrupt, which is concomitant with abrupt changes in the physical-chemical parameters. Overall, moisture content, total carbon (TC), pH, and electric conductivity (EC) were most predictive of microbial richness and diversity, while total sulfur (TS) and total phosphorous (TP) contents were additionally predictive of community composition. We also found statistically significant associations between taxa and soil properties, most of which involved moisture and TC contents. Our findings show that under-explored habitats for microbial survival and existence may prevail at greater soil depths near water or within water-bearing layers, a valuable substantiation also for the ongoing search for biosignatures on other planets, such as Mars.